2022
DOI: 10.1002/biof.1921
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive dietary components—Anti‐obesity effects related to energy metabolism and inflammation

Abstract: Obesity is the result of the long-term energy imbalance between the excess calories consumed and the few calories expended. Reducing the intake of energy dense foods (fats, sugars), and strategies such as fasting and caloric restriction can promote body weight loss. Not only energy in terms of calories, but also the specific composition of the diet can affect the way the food is absorbed and how its energy is stored, used or dissipated. Recent research has shown that bioactive components of food, such as polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 293 publications
(626 reference statements)
0
10
0
Order By: Relevance
“…We recommended shifting away from partially hydrogenated forms of coconut oil (a popular functional fat used in commercial products) and replacing these with extra-virgin, unrefined bioactive vegetable oils such as olive oil. We also provided options for fortification and recommendations to add specific nutrients, e.g., fatty acids and vitamins that are supportive of metabolic and brain health and function ( 98 , 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recommended shifting away from partially hydrogenated forms of coconut oil (a popular functional fat used in commercial products) and replacing these with extra-virgin, unrefined bioactive vegetable oils such as olive oil. We also provided options for fortification and recommendations to add specific nutrients, e.g., fatty acids and vitamins that are supportive of metabolic and brain health and function ( 98 , 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggested that long-term low grade inflammatory basis led to obesity and associated co-morbidities [ 99 , 100 ]. However, low and high dosage administration of vitamin A decrease TNF- α and IL6 on obese adults [ 101 ]; therefore, reducing insulin resistance, and improving energy expenditure [ 102 ].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Studies have shown that obese people have a higher basal metabolic volume, which may be because obese people have a larger base weight and need more energy to support their base [49,50]. Banquets or parties attended for business or personal reasons, usually held in the evening, are often attended by people who drink alcohol and consume ultra-processed foods.…”
Section: Multilevel Logistic Regression Analysismentioning
confidence: 99%